EFEKTIVITAS PENGGUNAAN METODE BERMAIN PASIR AJAIB DALAM MENSTIMULASI KEMAMPUAN MENULIS PERMULAAN PADA USIA 5-6 DI TK NURFADILLAH 1 - Afifah, Nurul; Bonita Mahmud; Fitrya Ali Imran (Institut Agama Islam Negeri Bone, 2026)
This study aimed to: (1) determine the early writing skills of children aged 5–6 years before the application of the magic sand play method at TK Nurfadillah 1; and (2) determine the early writing skills of children aged 5–6 years after the application of the magic sand play method at TK Nurfadillah 1. The research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The study was conducted at TK Nurfadillah 1, Kampuno Village, Barebbo District, Bone Regency, with a sample of 12 children. Data were collected through observation and tests related to early writing skills. The collected data were analyzed using SPSS for Windows version 25 to obtain descriptive statistics of the pretest and posttest results and to conduct hypothesis testing. The results showed that the use of the magic sand play method had an effect on stimulating early writing skills in children aged 5–6 years at TK Nurfadillah 1. Based on the results of the pretest and posttest analysis, it was found that the significance value (Sig. (2-tailed) = 0.000 < 0.05) and the calculated t-value (t_calculated = 7.423) was greater than the t-table value (t_table = 2.179), indicating that H? was accepted and H? was rejected. Therefore, it can be concluded that the magic sand play method has a significant effect on stimulating early writing skills in children aged 5–6 years at TK Nurfadillah 1, Kampuno Village, Barebbo District, Bone Regency. Keywords: Play Method; Magic Sand; Early Writing Skills; Early Childhoo